A lithium adsorbent, a preparation method and application thereof

By preparing magnesium-aluminum-doped lithium adsorbents in the presence of complexing agents, the problem of decreased adsorption capacity of aluminum-based lithium adsorbents in high-sulfate salt lake brines was solved, achieving uniform chemical composition distribution and cost reduction, making it suitable for large-scale lithium extraction.

CN119114006BActive Publication Date: 2026-11-06TIANQI LITHIUM SHEHONG CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411498476.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2026-11-06
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

When existing aluminum-based lithium adsorbents are used in high-sulfate salt lake brines, their adsorption capacity decreases significantly, and the preparation process suffers from problems such as uneven composition, high cost, and long process flow.

Method used

In the presence of a complexing agent, Al3+ and Mg2+ undergo complexation and co-precipitation to prepare magnesium-aluminum doped adsorbents, thereby improving their tolerance to high sulfate salt lake brines and achieving a uniform distribution of chemical components.

Benefits of technology

The prepared lithium adsorbent exhibits good tolerance in high sulfate salt lake brines, maintains stable adsorption capacity, is low in cost, and is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114006B_ABST
    Figure CN119114006B_ABST
Patent Text Reader

Abstract

This invention discloses a lithium adsorbent, its preparation method, and its application. The method for preparing the lithium adsorbent provided by this invention involves, in the presence of a complexing agent, causing Al... 3+ and Mg 2+ A magnesium-aluminum doped adsorbent is obtained by complexation co-precipitation. The above-described method for preparing lithium adsorbents involves adding a complexing agent to allow Al... 3+ and Mg 2+ Co-precipitation occurs under the action of a complexing agent, and magnesium is evenly distributed in the adsorbent. The prepared magnesium-aluminum-doped lithium adsorbent can improve its tolerance to high sulfate salt lake brine, and the chemical composition of the magnesium-aluminum-doped lithium adsorbent product is evenly distributed and the cost is lower.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium extraction materials technology, and more specifically, to a lithium adsorbent, its preparation method, and its application. Background Technology

[0002] Methods for extracting lithium resources from salt lake brines currently include salt field extraction, membrane extraction, adsorption, and extraction. Among these, adsorption is widely used due to its high selectivity and low pollution. Lithium adsorbents are classified into aluminum-based, manganese-based, and titanium-based adsorbents. Titanium-based and manganese-based adsorbents require acid to elute the adsorbed lithium, while aluminum-based lithium adsorbents do not require an acidic or alkaline environment for lithium adsorption and desorption, exhibiting advantages such as low solubility and low acid / alkali consumption. It is currently the only lithium adsorbent with industrial application, primarily used in chloride-type salt lake brines with high magnesium-to-lithium ratios.

[0003] In practical applications of aluminum-based lithium adsorbents, it has been found that when the sulfate concentration in the original brine is high, the adsorption capacity of the aluminum-based lithium adsorbent decreases significantly after multiple adsorption-desorption cycles, and it may even lose its adsorption capacity. Adsorbent doping is one method to improve the sulfate tolerance of the adsorbent. Currently, the preparation of doped aluminum-based lithium adsorbents still faces problems such as uneven composition, high cost, and long process flow. Summary of the Invention

[0004] The purpose of this invention is to overcome the defects of the prior art by providing a lithium adsorbent, its preparation method, and its application.

[0005] The technical problem solved by this invention is achieved by the following technical solution.

[0006] This invention provides a method for preparing a lithium adsorbent, which involves using a complexing agent to make Al... 3+ and Mg 2+ Complexation co-precipitation was performed to obtain magnesium-aluminum doped adsorbent.

[0007] The present invention also provides a lithium adsorbent prepared according to the above preparation method.

[0008] The present invention also provides an application of the lithium adsorbent prepared by the above preparation method or the lithium adsorbent prepared by the above method in extracting lithium ions from lithium-containing solutions.

[0009] The present invention has the following beneficial effects:

[0010] This invention provides a lithium adsorbent, its preparation method, and its application. The preparation method of the lithium adsorbent provided by this invention involves, in the presence of a complexing agent, causing Al... 3+ and Mg 2+ A magnesium-aluminum doped adsorbent is obtained by complexation co-precipitation. The above-described method for preparing lithium adsorbents involves adding a complexing agent to allow Al... 3+ and Mg2+ Coprecipitation occurs under the action of complexing agents, rather than Al. 3+ and Mg 2+ Separate precipitation: Doping magnesium into aluminum-based adsorbents can improve their tolerance to high sulfate salt lake brines, and the chemical composition of the product is more uniformly distributed, the preparation process is shorter, and the cost is lower. Attached Figure Description

[0011] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0012] Figure 1 This is a schematic diagram of the preparation process of lithium adsorbent;

[0013] Figure 2 The XRD patterns are of lithium adsorbents prepared using the methods provided in Examples 1-4. Detailed Implementation

[0014] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0015] The following is a detailed description of a lithium adsorbent, its preparation method, and its application provided by embodiments of the present invention.

[0016] In a first aspect, embodiments of the present invention provide a method for preparing a lithium adsorbent, which involves, in the presence of a complexing agent, causing Al... 3+ and Mg 2+ Complexation co-precipitation was performed to obtain magnesium-aluminum doped adsorbent.

[0017] Studies have shown that doping modification of aluminum-based adsorbents, such as introducing metal cations into the aluminum-based framework, can improve the structural stability of the adsorbent, increase the lithium mass transfer rate and adsorption capacity, thereby improving lithium extraction efficiency. However, in practical modification processes, some studies have proposed introducing Sc, Ga, Y, In, and La into aluminum-based adsorbents, but the cost of preparing adsorbents using raw materials containing these elements is too high, making it unsuitable for large-scale lithium extraction applications. Other studies have proposed preparing aluminum salt adsorbents containing polysaccharide compounds. This method involves directly adding an alkaline solution to a mixed solution of magnesium and aluminum salts for precipitation. Because the precipitation pH and hydroxide solubility product of magnesium and aluminum salts differ, direct precipitation results in separate precipitation of aluminum and magnesium salts, rather than co-precipitation. Furthermore, aluminum hydroxide is a colloid, which can easily lead to uneven distribution of the chemical composition of the product. Additionally, the use of polysaccharide compound solutions increases the process flow and cost.

[0018] Through practice and analysis, the inventor discovered that: Al 3+ The precipitate has a pH of 3.4–4.7, and the solubility product of Al(OH)3 is 1.9 × 10⁻⁶. -33 ;Mg 2+ The precipitation pH is 9.1–11.1, and the solubility product of Mg(OH)₂ is 1.2 × 10⁻⁶. -11 Therefore, Al 3+ Compared to Mg 2+ It is more prone to precipitation; if aluminum and magnesium salts are directly mixed with the precipitant, magnesium and aluminum will precipitate separately. Furthermore, Al(OH)3 is a colloid, and the subsequently formed Mg(OH)2 is difficult to disperse, easily causing the product's chemical composition to be unevenly distributed. To improve these defects, this invention provides a method for preparing a lithium adsorbent, in the presence of a complexing agent, making Al… 3+ and Mg 2+ Through complexation co-precipitation, magnesium is uniformly distributed in the aluminum-based adsorbent, resulting in a magnesium-doped aluminum-based adsorbent. The above method successfully incorporates magnesium into aluminum-based adsorbents via complexation precipitation, improving their tolerance to high-sulfate brine from salt lakes. Furthermore, the resulting lithium adsorbent product exhibits a more uniform chemical composition, lower cost, and is more suitable for large-scale applications.

[0019] In some optional embodiments, it includes: co-precipitating aluminum and magnesium by circulating a mixed solution containing aluminum salt, magnesium salt, lithium salt and complexing agent and an alkaline solution into water to obtain a magnesium-aluminum doped adsorbent.

[0020] In some alternative embodiments, the aluminum salt includes at least one of AlCl3 and Al(NO3)3, the magnesium salt includes at least one of MgCl2 and Mg(NO3)2, the lithium salt is LiCl, and the complexing agent is sulfosalicylic acid.

[0021] In some optional embodiments, the Al / Mg molar ratio in the mixed solution is 10–20, the Al / Li molar ratio is 1–2.5, and the amount of complexing agent is 1–1.5 times the molar amount of Al in the aluminum salt. During the complexation co-precipitation process, if the Al / Mg molar ratio is too high, the tolerance of the prepared lithium adsorbent to sulfate ions decreases; if the Al / Mg molar ratio is too low, the adsorption capacity of the prepared lithium adsorbent decreases. If the Al / Li molar ratio is too high, the adsorption capacity of the prepared lithium adsorbent decreases; if the Al / Li molar ratio is too low, the preparation cost increases. If the amount of complexing agent is too small, Al and Mg cannot co-precipitate sufficiently; if the amount is too large, the cost increases.

[0022] In some optional embodiments, the alkaline solution includes at least one of NaOH solution and KOH solution, and the concentration of the alkaline solution is 2-5 mol / L. During the complexation coprecipitation process, if the concentration of the alkaline solution is too low, the filtrate volume is large and the filtration time is long; if the concentration is too high, it is easy to cause local excess of alkali, aggravate pH fluctuations, and make the pH difficult to control.

[0023] In some optional embodiments, the temperature for complex coprecipitation is controlled at 70–90°C, and the final pH of the reaction is 9.5–11. During complex coprecipitation, if the precipitation temperature is too low, fewer Li particles will be embedded in the lithium adsorbent, resulting in a lower adsorption capacity; if the temperature is too high, energy consumption costs will increase. If the final pH is too low, the reactants will not precipitate completely; if the final pH is too high, the generated Al(OH)3 will dissolve.

[0024] In some optional embodiments, the method further includes: rinsing the filter cake after filtering the reaction solution with an equal mass of water once, stirring twice, and then drying the washed filter cake at 105°C to obtain a magnesium-aluminum doped adsorbent.

[0025] Secondly, embodiments of the present invention provide a lithium adsorbent prepared according to the above-described preparation method.

[0026] In some optional embodiments, the lithium adsorbent has a lithium adsorption capacity of 6–14 mg / g for SO4. 2- After 30 adsorption-desorption cycles, the adsorption capacity of brine with a content of 40 g / L or higher decreases by 6% to 14%.

[0027] Thirdly, embodiments of the present invention provide an application of a lithium adsorbent prepared by the above preparation method or the above-mentioned lithium adsorbent in extracting lithium ions from a lithium-containing solution.

[0028] In some alternative embodiments, the lithium-containing solution includes at least one of salt lake brine, groundwater, seawater, or industrial lithium-containing wastewater.

[0029] In some optional embodiments, the brine type includes at least one of lithium chloride brine, lithium sulfate brine, and high sulfate brine, preferably high sulfate brine.

[0030] The present invention will be further described below with reference to embodiments.

[0031] A method for preparing a lithium adsorbent, see [link to relevant documentation]. Figure 1 This includes the following steps:

[0032] 1. Prepare a mixed solution by mixing aluminum salts (anhydrous or hydrated AlCl3, Al(NO3)3), magnesium salts (anhydrous or hydrated MgCl2, Mg(NO3)2), LiCl, and a complexing agent (sulfosalicylic acid), wherein the Al / Mg molar ratio is 10–20 and the Al / Li molar ratio is 1–2.5. The complexing agent is added at a ratio of 1–1.5 times the molar amount of Al in the aluminum salt.

[0033] 2. Prepare an alkaline solution by dissolving the base (NaOH, KOH) in water to a concentration of 2–5 mol / L.

[0034] 3. Add the mixed solution and the alkaline solution to a certain amount of water in parallel, keep the temperature at 70-90℃, and carry out the complexation coprecipitation reaction at the pH of 9.5-11 at the reaction endpoint.

[0035] 4. After the reaction is complete, the filter cake obtained by filtration is rinsed once with an equal mass of water and stirred twice.

[0036] 5. The washed filter cake is dried at 105℃ to obtain a magnesium-aluminum doped adsorbent.

[0037] Example 1

[0038] A method for preparing a lithium adsorbent includes the following steps:

[0039] 1. Prepare a 1.5 L mixed solution by mixing 0.5 mol anhydrous AlCl3, 0.05 mol anhydrous MgCl2, 0.5 mol LiCl, and 0.75 mol sulfosalicylic acid as a complexing agent, wherein the Al / Mg molar ratio is 10 and the Al / Li molar ratio is 1. The complexing agent is added at 1.5 times the molar amount of Al.

[0040] 2. Prepare a 4 mol / L NaOH solution.

[0041] 3. Add the mixed solution and the alkali solution to 0.5L of water at a flow rate of 1L / h. Adjust the flow rate of the alkali solution according to the pH of the solution, keep the temperature at 90℃, and carry out the complexation coprecipitation reaction when the final pH of the reaction is 9.5.

[0042] 4. After the reaction is complete, rinse the filter cake after filtering the reactants once with an equal mass of water and stir twice.

[0043] 5. The washed filter cake was dried at 105℃ to obtain a magnesium-aluminum doped adsorbent, denoted as sample a.

[0044] Example 2

[0045] A method for preparing a lithium adsorbent includes the following steps:

[0046] 1. Prepare a 0.5 L mixed solution by mixing 0.2 mol AlCl3·6H2O, 0.01 mol MgCl2·6H2O, 0.16 mol LiCl and 0.2 mol complexing agent sulfosalicylic acid, wherein the Al / Mg molar ratio is 20, the Al / Li molar ratio is 1.25, and the complexing agent is added at a molar amount equal to that of Al.

[0047] 2. Prepare a 5 mol / L solution of NaOH.

[0048] 3. Add the mixed solution and the alkali solution to 0.5L of water at a flow rate of 0.5L / h. Adjust the flow rate of the alkali solution according to the pH of the solution, maintain the temperature at 80℃, and carry out the complexation coprecipitation reaction when the pH of the reaction endpoint is 11.

[0049] 4. After the reaction is complete, rinse the filter cake after filtering the reactants once with an equal mass of water and stir twice.

[0050] 5. The washed filter cake was dried at 105℃ to obtain a magnesium-aluminum doped adsorbent, denoted as sample b.

[0051] Example 3

[0052] A method for preparing a lithium adsorbent includes the following steps:

[0053] 1. Prepare a 1 L mixed solution by mixing 0.3 mol Al(NO3)3·9H2O, 0.02 mol Mg(NO3)2·6H2O, 0.12 mol LiCl and 0.36 mol complexing agent sulfosalicylic acid, wherein the Al / Mg molar ratio is 15, the Al / Li molar ratio is 2.5, and the complexing agent is added at 1.2 times the molar amount of Al.

[0054] 2. Prepare a 3 mol / L NaOH solution.

[0055] 3. Add the mixed solution and the alkali solution to 1L of water at a flow rate of 1L / h. Adjust the flow rate of the alkali solution according to the pH of the solution, maintain the temperature at 75℃, and carry out the complexation coprecipitation reaction when the pH of the reaction endpoint is 10.

[0056] 4. After the reaction is complete, rinse the filter cake after filtering the reactants once with an equal mass of water and stir twice.

[0057] 5. The washed filter cake was dried at 105℃ to obtain a magnesium-aluminum doped adsorbent, denoted as sample c.

[0058] Example 4

[0059] A method for preparing a lithium adsorbent includes the following steps:

[0060] 1. Prepare a 1 L mixed solution by dissolving 0.3 mol Al(NO3)3·9H2O, 0.02 mol Mg(NO3)2·6H2O, 0.12 mol LiCl, and 0.36 mol sulfosalicylic acid as a complexing agent. The Al / Mg molar ratio is 15, and the Al / Li molar ratio is 2.5. The complexing agent is added at 1.2 times the molar amount of Al.

[0061] 2. Prepare a 2 mol / L solution of the base KOH.

[0062] 3. Add the mixed solution and the alkali solution to 0.75L of water at a flow rate of 0.5L / h. Adjust the flow rate of the alkali solution according to the pH of the solution, maintain the temperature at 70℃, and carry out the complexation coprecipitation reaction when the pH of the reaction endpoint is 10.

[0063] 4. After the reaction is complete, rinse the filter cake after filtering the reactants once with an equal mass of water and stir twice.

[0064] 5. The washed filter cake was dried at 105℃ to obtain a magnesium-aluminum doped adsorbent, denoted as sample d.

[0065] The XRD patterns of the lithium adsorbents prepared using the methods in Examples 1-4 are shown below. Figure 2 ,from Figure 2 The presence of Mg(OH)2 diffraction peaks in the lithium adsorbent indicates that Mg exists in the prepared lithium adsorbent in the form of Mg(OH)2.

[0066] Comparative Example 1

[0067] A method for preparing a lithium adsorbent includes the following steps:

[0068] 1. Prepare a 0.5 L mixed solution by dissolving 0.1 mol anhydrous AlCl3, 0.004 mol anhydrous MgCl2, 0.2 mol LiCl, and 0.05 mol sulfosalicylic acid, wherein the Al / Mg molar ratio is 25 and the Al / Li molar ratio is 0.5. Add a complexing agent at 0.5 times the molar amount of Al.

[0069] 2. Prepare a 1 mol / L NaOH solution.

[0070] 3. Add the mixed solution and the alkali solution to 1L of water at a flow rate of 0.5L / h. Adjust the flow rate of the alkali solution according to the pH of the solution, keep the temperature at 60℃, and carry out the complexation coprecipitation reaction when the pH of the reaction endpoint is 9.

[0071] 4. After the reaction is complete, rinse the filter cake after filtering the reactants once with an equal mass of water and stir twice.

[0072] 5. The washed filter cake was dried at 105℃ to obtain a magnesium-aluminum doped adsorbent, denoted as sample e.

[0073] Comparative Example 2

[0074] A method for preparing a lithium adsorbent includes the following steps:

[0075] 1. Prepare a 1.5 L mixed solution by mixing 1 mol Al(NO3)3·9H2O, 0.2 mol Mg(NO3)2·6H2O, 0.33 mol LiCl, and 2 mol sulfosalicylic acid as a complexing agent. The Al / Mg molar ratio is 5, and the Al / Li molar ratio is 3. The complexing agent is added at twice the molar amount of Al.

[0076] 2. Prepare a 6 mol / L KOH solution.

[0077] 3. Add the mixed solution and the alkali solution to 500 mL of water at a flow rate of 1 L / h. Adjust the flow rate of the alkali solution according to the pH of the solution, keep the temperature at 95℃, and carry out the complexation coprecipitation reaction when the pH of the reaction endpoint is 12.

[0078] 4. After the reaction is complete, rinse the filter cake after filtering the reactants once with an equal mass of water and stir twice.

[0079] 5. The washed filter cake was dried at 105℃ to obtain a magnesium-aluminum doped adsorbent, denoted as sample f.

[0080] Comparative Example 3

[0081] A method for preparing a lithium adsorbent includes the following steps:

[0082] 1. Prepare a 1.5 L mixed solution by mixing 0.5 mol anhydrous AlCl3, 0.05 mol anhydrous MgCl2, and 0.5 mol LiCl, wherein the Al / Mg molar ratio is 10 and the Al / Li molar ratio is 1.

[0083] 2. Prepare a 2 mol / L NaOH solution.

[0084] 3. Add the mixed solution and the alkali solution to 1L of water at a flow rate of 1L / h. Adjust the flow rate of the alkali solution according to the pH of the solution, keep the temperature at 90℃, and carry out the coprecipitation reaction when the final pH is 9.5.

[0085] 4. After the reaction is complete, rinse the filter cake after filtering the reactants once with an equal mass of water and stir twice.

[0086] 5. The washed filter cake was dried at 105℃ to obtain magnesium-aluminum doped adsorbent, denoted as sample g.

[0087] Comparative Example 4

[0088] A method for preparing a lithium adsorbent includes the following steps:

[0089] A lithium adsorbent was prepared using the method provided in CN108993376A, and denoted as sample h.

[0090] The determination of sample adsorption capacity includes the following steps:

[0091] 1. Take 10g of each lithium adsorbent sample numbered a to h and add it to 500mL of brine. Stir at 200rpm for 3h.

[0092] 2. Separate the lithium adsorbent and brine by filtration, and send the filtrate for analysis. Rinse once with an equal volume of deionized water to remove any entrained brine.

[0093] 3. Place the lithium adsorbent in 500 mL of deionized water, stir at 200 rpm for 3 hours to desorb the lithium ions in the adsorbent, filter and separate, and send the desorbed solution for analysis.

[0094] 4. Steps 1 to 3 constitute one adsorption-desorption process. Repeat the above adsorption-desorption process 30 times.

[0095] The composition of the brine used for adsorption in the above embodiments and comparative examples during the determination of sample adsorption capacity is shown in Table 1 below.

[0096] Table 1

[0097] Li Na K Ca Mg Al <![CDATA[SO4 2- ]]> <![CDATA[Cl - ]]> B 0.42 72.7 83.5 0.36 14.5 ND 44.2 158.6 0.17

[0098] The composition of the samples prepared in the above embodiments and comparative examples is shown in Table 2 below.

[0099] Table 2

[0100] Sample Name Li / % Al / % Mg / % Cl / % Sample a 4.38 28.08 2.32 21.77 Sample b 3.54 29.11 1.27 17.95 Sample c 2.47 28.54 1.64 12.40 Sample d 1.85 28.29 1.59 9.29 Sample e 5.93 26.95 0.31 30.07 Sample f 1.61 27.35 3.13 8.19 sample g 4.31 28.16 0.86 21.68 Sample h 2.05 28.84 - 10.21

[0101] The adsorption capacity of the samples prepared in the above examples and comparative examples for lithium in brine is shown in Table 3 below.

[0102] Table 3

[0103]

[0104]

[0105] Combining Tables 2 and 3 above, it can be seen that the samples synthesized in Examples 1-4 of this invention exhibited a 6%-14% decrease in adsorption capacity after 30 adsorption-desorption cycles. The lithium adsorbents prepared using the methods provided in Comparative Examples 1-3 showed a decrease in adsorption capacity or an increased rate of capacity reduction. The lithium adsorbent prepared using the method provided in Comparative Example 4 not only showed a decrease in adsorption capacity but also exhibited a 71% decrease in adsorption capacity after 30 adsorption-desorption cycles. This indicates that the lithium adsorbents synthesized using the schemes provided in the embodiments of this invention have good tolerance to high-sulfate salt lake brines.

[0106] The raw material usage and cost of Examples 1 and 2 of Patent CN117000199A are compared with those of Examples 1 and 2 of this invention. The results are shown in Table 4 below.

[0107] Table 4

[0108]

[0109] As can be seen from Table 4 above, the cost of the lithium adsorbent synthesized by the methods provided in Examples 1 and 2 of this invention is much lower than the synthesis cost of patent CN117000199A. This indicates that the lithium adsorbent prepared by the scheme provided in the examples of this invention has the advantage of low cost, which is conducive to its widespread application in the field of lithium extraction from lithium-containing solutions.

[0110] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a lithium adsorbent, characterized in that, It is in the presence of a complexing agent that Al 3+ and Mg 2+ The process involves co-precipitating a complex with aluminum, magnesium, lithium salts and a complexing agent, and then simultaneously introducing an alkaline solution into water to co-precipitate the aluminum and magnesium complexes, thereby obtaining a magnesium-aluminum doped adsorbent. The mixed solution contains an Al / Mg molar ratio of 10-20 and an Al / Li molar ratio of 1-2.

5. The amount of the complexing agent is 1-1.5 times the molar amount of Al in the aluminum salt, and the final pH of the reaction is controlled to be 9.5-11.

2. The preparation method according to claim 1, characterized in that, The aluminum salt includes at least one of AlCl3 and Al(NO3)3, the magnesium salt includes at least one of MgCl2 and Mg(NO3)2, the lithium salt is LiCl, and the complexing agent is sulfosalicylic acid.

3. The preparation method according to claim 1, characterized in that, The alkaline solution includes at least one of NaOH solution and KOH solution.

4. The preparation method according to claim 3, characterized in that, The concentration of the alkaline solution is 2~5 mol / L.

5. The preparation method according to claim 1, characterized in that, The temperature for complexation co-precipitation is controlled at 70~90℃.

6. The preparation method according to claim 5, characterized in that, Also includes: The filter cake after filtering the reaction solution was rinsed once with an equal mass of water and stirred twice. The washed filter cake was then dried at 105℃ to obtain a magnesium-aluminum doped adsorbent.

7. A lithium adsorbent prepared by any one of claims 1-6.

8. The lithium adsorbent according to claim 7, characterized in that, The lithium adsorbent has a lithium adsorption capacity of 6~14 mg / g, and for SO4 2- After 30 adsorption-desorption cycles, the adsorption capacity of brine with a content of 40 g / L or higher decreases by 6% to 14%.

9. The application of the lithium adsorbent prepared by the preparation method according to any one of claims 1-6 or the lithium adsorbent according to any one of claims 7-8 in the extraction of lithium ions from lithium-containing solutions.

10. The application according to claim 9, characterized in that, The lithium-containing solution includes at least one of salt lake brine, groundwater, seawater, or industrial lithium-containing wastewater.

11. The application according to claim 10, characterized in that, The brine type of the salt lake includes at least one of lithium chloride brine, lithium sulfate brine, and high sulfate brine.

12. The application according to claim 11, characterized in that, The brine in the salt lake is of the high sulfate type.

Citation Information

Patent Citations

  • Aluminum salt lithium adsorbent, and preparation method and application thereof

    CN108993376A

  • Gel adsorbent for lithium extraction of salt lake brine with high magnesium-lithium ratio and preparation method

    CN108607500A

  • Lithium-aluminum adsorption material prepared from salt lake brine with high magnesium-to-lithium ratio and method of lithium-aluminum adsorption material

    CN115739004A